PENDIDIKAN POLITIK VERSUS PARTISIPASI POLITIK DIERA INDUSTRI 4.0 - Dalintang Ketut Dwi Saputri; Rika Puspita Saputri; Anita Trisiana (Universitas Slamet Riyadi, 2022)
The industrial revolution has changed the way work will be automatically through innovations. The industries participate actively as the identity organization with vision to win profit. Revolusi, based on industry walking with political system education where in paradikma there are major changes in the political system education and potential be increased. In political education can be made people understand political 4.0 in the industrial era, the progress we can see in country it makes society, more active will the development of very streaked with technology that sophisticated and society must be careful will political progress diera industrial because it will lead to a in want if not in use it well.